POVERTY AND STUDENTS’ ACADEMIC ACHIEVEMENT IN PAPUA, INDONESIA - Saifullah, Saifullah; Yawan, Hendri (Sanata Dharma University Yogyakarta, 2022)
Poverty in Indonesia has experienced a continual decrease in the last decades. However, the numbers of people living under the poverty line in the country are still constant at above 10 percent. The study intended to review the influence of poverty on students' academic achievements in Papua. The study aims to explore the measurement of poverty, types of poverty, poverty and its effect in Papua, how poverty affects students’ academic achievements, and possible recommendations. Some research studies have found how poverty negatively disturbs the students' academic achievements. The results indicate that poverty affects students’ academic achievements in Papua and even leads them to school dropout. Becoming one of Indonesia's most impoverished regions with a high poverty rate, the academic achievement among students in Papua is highly correlated with poverty, health and safety issues, food security, parental behaviour, acute, chronic and stressor, and social and emotional challenges. Such situations later decrease their academic achievements in school.